2014
DOI: 10.3329/updcj.v3i2.17996
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Accuracy and Reproducibility of Alginate and Addition Reaction Silicone as an Impression Materials.

Abstract: Background: To achieve accuracy and exact reproduction of prosthesis, choosing a perfect impression material is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…With several competing modalities currently available, some authors have suggested that the profession should determine the best alternative to traditional plaster models. 5 The accuracy of impressions obtained by addition silicone impression material is well proven and documented according to Shakila Fatema et al 6,7 On basis of these studies, and better reproducibility of the dental structures, addition silicone rubber base impression (DMG Honigum putty) material was used in this study to take impressions of the maxillary and mandibular arch. Studies were done on accuracy, validity, reliability, and reproducibility of linear dental measurements of digital models obtained from scans of 'Alginate' impressions and plaster models, results showed that digital models are valid, reliable, and reproducible methods to obtain dental measurements for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 95%
“…With several competing modalities currently available, some authors have suggested that the profession should determine the best alternative to traditional plaster models. 5 The accuracy of impressions obtained by addition silicone impression material is well proven and documented according to Shakila Fatema et al 6,7 On basis of these studies, and better reproducibility of the dental structures, addition silicone rubber base impression (DMG Honigum putty) material was used in this study to take impressions of the maxillary and mandibular arch. Studies were done on accuracy, validity, reliability, and reproducibility of linear dental measurements of digital models obtained from scans of 'Alginate' impressions and plaster models, results showed that digital models are valid, reliable, and reproducible methods to obtain dental measurements for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 95%
“…However, dental impression materials made of alginate are not as hard as those made of silicon because they contain a high amount of water during preparation. On the other hand, silicone dental impression materials are known to take impressions with high reliability [ 8 ]. Our present findings demonstrated that the HU values of silicon material varied widely from 574.2 HU to 3183.9 HU.…”
Section: Discussionmentioning
confidence: 99%
“…When compared against the test die. [48] According to Amin et al , stone cast obtained from PVS impression material after disinfection with 2% GA and 1% SH showed satisfactory surface detail reproduction. [9] Further studies are needed in order to evaluate the surface detail reproduction of PVS impressions when treated with different disinfectant agents.…”
Section: Discussionmentioning
confidence: 99%
“…[7114546] In addition to the measurement of dimensional accuracy, few studies have also examined the surface detail reproduction of the impressions and gypsum casts. [94748]…”
Section: Introductionmentioning
confidence: 99%